2023
DOI: 10.1111/dar.13720
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of adolescents' perspectives on peer and influencer alcohol‐related posts on social media

Abstract: IntroductionAdolescent exposure to alcohol‐related content on social media is common and associated with alcohol use and perceived norms; however, little is known about how exposure differs by the source of the content (e.g., peer or ‘influencer’). The purpose of this study was to utilise qualitative methods to compare adolescent perspectives on peer‐ versus influencer‐generated alcohol content on social media.MethodsNine virtual semi‐structured focus groups were conducted with adolescents (aged 15–19 years), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In this special section, a range of research methods (e.g., focus groups, social media data collection), populations (e.g., adolescents) and social media platforms (e.g., Twitter, TikTok) were studied to dig deeper into how "positive" posts about substances may be. For example, Corcoran et al's [4] focus group study aligned with prior work and found that adolescents reported that alcohol-related posts on social media convey drinking as acceptable, normal and cool [4]. Similarly, Lim et al's [5] content analysis of medicinal-cannabis-related tweets showed that tweets touting the therapeutic value of cannabis are twice as common as those referencing intoxication and withdrawal.…”
Section: What Do People See?mentioning
confidence: 77%
“…In this special section, a range of research methods (e.g., focus groups, social media data collection), populations (e.g., adolescents) and social media platforms (e.g., Twitter, TikTok) were studied to dig deeper into how "positive" posts about substances may be. For example, Corcoran et al's [4] focus group study aligned with prior work and found that adolescents reported that alcohol-related posts on social media convey drinking as acceptable, normal and cool [4]. Similarly, Lim et al's [5] content analysis of medicinal-cannabis-related tweets showed that tweets touting the therapeutic value of cannabis are twice as common as those referencing intoxication and withdrawal.…”
Section: What Do People See?mentioning
confidence: 77%
“…This study also suggests that we may be seeing similar patterns of engagement with SMI marketing across a range of harmful industries. For example, alcohol researchers have argued that while young people may feel a personal connection to SMIs, the lack of offline relationship with the SMI may make it difficult for young people to critically evaluate SMI content for realism and authenticity ( Corcoran et al ., 2023 ). Developing integrated approaches to research and policy which consider and examine how these strategies may be used and applied across a range of industries will be important in progressing comprehensive policy frameworks which focus on harmful marketing tactics as well as responses to specific industries or products.…”
Section: Discussionmentioning
confidence: 99%
“…Celebrity marketing of harmful products has included the use of SMIs on platforms popular with young people such as TikTok, YouTube and Instagram ( Chwasta, 2022 ; Lee et al ., 2023 ; Vassey et al ., 2023 ). These types of marketing are persuasive for young people, and may influence the normalization and consumption of these products ( Hendriks et al ., 2020 ; Packer et al ., 2022 ; Corcoran et al ., 2023 ; Smith and Hilton, 2023 ), as well as promoting new products, and reaching young people who otherwise would not be exposed to these promotions ( Campaign for Tobacco-Free Kids, 2023 ).…”
Section: Introductionmentioning
confidence: 99%